Apoptotic pathways in mammals - Green, Douglas (Henry Stewart Talks, 2007)
Apoptosis and programmed cell death, Apoptosis: developmental signals, damage or stress, loss of adhesion and oncogenesis, Caspases: inactive and active, Death folds, Inhibitors of apoptosis proteins, Death receptor (extrinsic) pathway, Mitochondrial (intrinsic) pathway, The Bcl-2 family proteins, Apoptosome, Activation, repression and de-repression, Caspase-independent cell death, Cells die in the absence of caspase activation
Archived at 2020/08/13